(20S)-24,25-Dihydroxy-20,24-epoxy-3,4-secodammar-4(28)-en-3-oic acid from Aglaia smithii - Harneti, D.; Supratman, U.; Mukhtar, M.R.; Awang, K.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(30)H(50)O(5), was isolated from the bark of Aglaia smithii. There are two independent molecules in the asymmetric unit that differ in the orientation of the isopropenyl group attached to the cyclohexane ring. The cyclohexane rings in both molecules adopt chair conformations, whereas the cyclopentane and tetrahydrofuran rings adopt envelope conformations. The independent molecules are linked into a layer parallel to (010) by O-H center dot center dot center dot O hydrogen bonds.